Теоретичні засади виділення права загальної спадщини людства в окрему галузь міжнародного права - Каткова, Т. Г.; Каткова, Т. Г.; Katkova, Т. (My University, 2013)
The article is devoted to consideration of theoretical bases of selection the law of the Common Heritage of Mankind in the separate field of international law. The author characterizes the stages of becoming and development the law of the Common Heritage of Mankind, and also analyses structural elements necessary for the selection of this right in the separate field of law.
Каткова Т. Г. Теоретичні засади виділення права загальної спадщини людства в окрему галузь міжнародного права / Т. Г. Каткова // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 93-102.
Keywords: право загальної спадщини людства; етапи становлення і розвитку права загальної спадщини людства; структурні елементи права загальної спадщини людства; право общего наследия человечества; этапы становления и развития права общего наследия человечества; структурные элементы права общего наследия человечества; right common heritage of mankind; stages of formation and development of the right common heritage of mankind; structural elements of the right common heritage of mankind